A Study of English Proficiency Test among the First Year University Students - Ignasia Yuyun; Meyling Meyling; Naftalia Laksana; Demus Abenedgo (Journal of Language and Literature, 2018)
The study aims at analyzing the English skills in an English Proficiency Test (EPT) shown bystudents at tertiary level or university students, particularly the first year university students (freshmen).The study centers around the students English skills represented in English Proficiency Test, which arethen related to the students common problems investigated in this study. The three sections in EnglishProficiency Test analyzed in this study including listening, structure and written expressions, andreading. This study revealed reading skill was the major problems faced by the first year of universitystudents, particularly, in reviewing overall reading text. To solve this problem, the cognitive strategies,particularly the top-down reading strategies are suggested to anticipate the authors purpose, previewthe text, think about what one already knows about the topic, skim for main points, etc. An effectivereading strategies training which is more focused and explicit should be regularly practiced andenhanced since it can significantly boost reading proficiency and language acquisition.Keywords: English Proficiency Test, university student